Gender disparities in the downstream nodes of the rice value chain in Eastern Uganda: Roles, labour, time allocation, and empowerment - Oloo, Augustine (Makerere University, 2024)
Developing country governments and development organizations have labored to integrate both men and women in post-production value chains as a strategy for poverty alleviation, economic growth, employment generation, gender equality, and improved well-being. Despite the rapid mainstreaming of inclusiveness in policy discourse, remarkably little literature sheds light on the changes over time in post-production agricultural value chains. This study addresses this gap. Using data collected from 515 downstream rice value chain actors in Eastern Uganda, the study analyzes the distribution of roles, allocation of time, and empowerment among women and men. It also assesses the determinants of their time allocation to the downstream nodes of the rice value chain using linear regression. To account for endogeneity, the study used the two-step control function approach in the treatment-effects model to determine the effect of engagement in downstream nodes of the rice value chain on the empowerment of men and women. Results showed that the downstream nodes of the rice value chain and most of the activities are dominated by men. Women on the other hand dominated activities that were less renumerated such as sorting and cleaning rice and preparing food for workers. Findings on time allocation showed that men and women spend 5-8 hours per day in the downstream nodes of the rice value chain with men spending significantly more time than women. Time allocation to the downstream nodes of the rice value chain depends on the sex of the actor, association membership, engagement in non-agricultural activities, engagement in rice production, and marital status. The Individual Empowerment Index showed that the mean individual empowerment score for men is significantly higher than for women. Men are also more empowered than women in the income, leadership, and time allocation domains. Women on the other hand are more empowered than men in the household livelihood domain. Engagement in milled rice trading was found to significantly lower the empowerment scores of women. The study recommends efforts to increase women’s visibility in post-production nodes of agricultural value chains. The study recommends strategies such as improvement in infrastructure that reduces household labor, such as reliable water and electricity supply to reduce the domestic work burden for women, enabling them to invest more time in productive. The study also recommends the creation of gender awareness through education especially in the early years to eliminate stereotypes.